1979
DOI: 10.1111/j.1440-1827.1979.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Gastric Glands in the Submucosa of the Stomach

Abstract: The submucosal heterotopic gastric glands were found in 160 cases (10.7%) of 1500 resected stomachs; 15y0 in gastric ulcer, 9.9% in gastric carcinoma, 4% in duodenal ulcer and 11% in chronic gastritis. The heterotopic glands were usually found in the distal half of the stomach, diffusely or localized. Macroscopic submucosal tumor was found in 9 (5%) of 160 cases. Although the heterotopic glands were found with an intimate relation to the repeated mucosal damage and subsequent intestinal metaplasia, they had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 3 publications
6
44
0
Order By: Relevance
“…The heterotopic lesions are considered to be congenital malformations 12 or secondary invasion of surface mucosa through a defect of the muscularis mucosa, which arises as a result of inflammation or ulceration. 13,14 Similar submucosal glands were observed in a peculiar gastric lesion occurring at a gastroenteric anastomosis, known as gastritis cystic polyposa 15 or polypoid hypertrophic gastritis, 16,17 with prolapse of the gastric mucosa into the stoma and consequent glandular proliferation considered to be a cause of the lesion. A lesion with some morphological similarities was noted in the lower intestinal tract, and fermed colitis cystica profunda 18,19 and enteritis cystica polyposa.…”
Section: Discussionmentioning
confidence: 98%
“…The heterotopic lesions are considered to be congenital malformations 12 or secondary invasion of surface mucosa through a defect of the muscularis mucosa, which arises as a result of inflammation or ulceration. 13,14 Similar submucosal glands were observed in a peculiar gastric lesion occurring at a gastroenteric anastomosis, known as gastritis cystic polyposa 15 or polypoid hypertrophic gastritis, 16,17 with prolapse of the gastric mucosa into the stoma and consequent glandular proliferation considered to be a cause of the lesion. A lesion with some morphological similarities was noted in the lower intestinal tract, and fermed colitis cystica profunda 18,19 and enteritis cystica polyposa.…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4][5] GCP may present as a subepithelial tumor or a polyp, but rarely as a giant gastric mucosal fold. 6,7 GCP is usually regarded as a benign lesion, 3,4,8 but there are some controversies about its malignant potential. There have been some reports of cases about GCP accompanied by gastric carcinoma or adenoma with high grade dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Iwanaga et al suggested that submucosal cysts may not be precancerous lesions, but be paracancerous [2]. However, there are several reports that submucosal cysts of the stomach have no specific association to gastric carcinogenesis [6,9]. If these cysts are paracancerous lesions, the patient reported herein will likely present with carcinoma in the gastric remnant in the future and careful surveillance will be necessary.…”
Section: Discussionmentioning
confidence: 91%
“…The diffuse heterotopic submucosal cystic malformations (submucosal cysts) of the stomach have been reported under several names, including multiple diffuse cystic disease [1], diffuse submucosal cystic disease [2], diffuse cystic glandular malformation [3], heterotopic gastric glands [6], and heterotopic submucosal gastric cysts [7]. These cysts have been found in stomachs resected for gastric carcinoma, and their possible association with gastric carcinoma has been suggested [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation